Ball tip feeler vs. depth gauge: detection of bony pedicle defects before pedicle screw insertion - Brunnemer, Ulf; Roth, Sabine; Müller, Christian W.; Hüfner, Tobias; Decker, Sebastian (In vivo, 2025)
Background/Aim: The objective of this study was to investigate whether the detection rates of pedicle breaches depended on the surgeon’s experience level and whether different instruments resulted in varied palpation quality. - Materials and Methods: Experienced surgeons (ES) (n=8) and inexperienced surgeons (IS) (n=10) were compared. The study was performed using a sawbone model of the spine. Pedicle defects were created at various positions and levels. Participants detected and located the bony defects using a depth gauge and a straight ball tip feeler. After the first measurement, the IS group underwent training focused on identifying bone defects. The experiment was repeated after three weeks under identical conditions. - Results: A significant difference was found between ES and IS in the time required to palpate pedicles and bony defects using the ball tip feeler during the first measurement (297.2±114.4 s vs. 202.1±77.9 s; p=0.05). However, after training and during the second measurement three weeks later, these differences were no longer observed (223.7±65.1 s vs. 212.2±73.6 s; p=0.73). Notably, no significant differences were found in the accuracy in detecting bony pedicle defects between the two groups, regardless of the device used. Furthermore, no improvement was found in the IS group after training, regardless of the device used. - Conclusion: ES and IS accurately detected pedicle breaches without significant differences. Training did not affect detection rates between the groups, and the choice of device did not affect the accuracy of pedicle breach detection.
Gesehen am 23.07.2025